2008
DOI: 10.1016/j.janxdis.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine reduces social anxiety in individuals with a co-occurring alcohol use disorder

Abstract: Patients with social anxiety disorder who are seen in clinical practice commonly have additional psychiatric comorbidity, including alcohol use disorders. The first line treatment for social anxiety disorder is selective-serotonin-reuptake-inhibitors (SSRIs), such as paroxetine. However, the efficacy of SSRIs has been determined with studies that excluded alcoholics. Forty two subjects with social anxiety and a co-occurring alcohol use disorder participated in a 16-week, double-blind, placebo-controlled clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 34 publications
1
46
1
1
Order By: Relevance
“…In a social phobia study with children and adolescents 12Á17 years of age, paroxetine was superior to placebo . In small DBPC studies in patients with a double diagnosis of SAD and alcohol use, paroxetine showed an effect on social anxiety and on alcohol use (Book et al 2008;Randall et al 2001). In a relapse prevention study, responders were randomized to a further 24 weeks of paroxetine or placebo in the extension of a 12-week single-blind treatment with paroxetine.…”
Section: Summary Of Recommendations For the Treatment Of Gadmentioning
confidence: 99%
“…In a social phobia study with children and adolescents 12Á17 years of age, paroxetine was superior to placebo . In small DBPC studies in patients with a double diagnosis of SAD and alcohol use, paroxetine showed an effect on social anxiety and on alcohol use (Book et al 2008;Randall et al 2001). In a relapse prevention study, responders were randomized to a further 24 weeks of paroxetine or placebo in the extension of a 12-week single-blind treatment with paroxetine.…”
Section: Summary Of Recommendations For the Treatment Of Gadmentioning
confidence: 99%
“…This approach reasonably assumes that reducing AnxD symptoms should reduce the AUD relapse risk associated with AnxD. It has become increasingly clear, however, that this common sense approach has largely failed to improve AUD outcomes significantly for those with a co-occurring AnxD (Book et al, 2008; Bowen et al, 2000; Hobbs et al, 2011; Randall et al, 2001; Schade et al, 2005; Thomas et al, 2008). For example, Hobbs et al (2011) conducted a meta-analysis of 15 controlled randomized studies testing the value of augmenting AUD treatment with either cognitive behavioral therapy (CBT) or medications for a co-occurring AnxD.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the first paroxetine trial, anxiety symptoms improved a significantly greater degree in the active medication group, but there was no effect on drinking outcome measures (18). The second paroxetine trial had similar results in reducing anxiety symptoms, but alcohol use outcomes were not reported (19).…”
Section: Introductionmentioning
confidence: 85%
“…Four double-blind placebo-controlled trials have studied the use of buspirone to treat alcohol dependence and co-morbid generalized anxiety disorder or anxiety symptoms (14)(15)(16)(17). Two randomized placebo-controlled trials have evaluated paroxetine for alcohol use disorders and comorbid social phobia (18,19). In three of the four buspirone studies, the medication was effective in reducing anxiety symptoms (14,15,17).…”
Section: Introductionmentioning
confidence: 99%